Laser-guided percutaneous microwave ablation for lung nodules: a promising approach with reduced operation time - Zhang, Yuejuan; Li, Zijian; Ding, Cheng; Zhao, Jun; Ye, Li; Shen, Ziqing; Song, Xinyu (BMC surgery, 2024)
Background Pulmonary nodule ablation is an effective method for treating pulmonary nodules. This study is based on the traditional CT-guided percutaneous microwave ablation (MWA) of pulmonary nodules. By comparing laser guidance technology with freehand method, this study aims to explore the safety and efficacy and patients’ pain scores of these two approaches. Methods This study retrospectively analyzed 126 patients who underwent CT-guided percutaneous lung ablation at the First Affiliated Hospital of Soochow University from April 2020 to April 2024. Based on the guidance method, we divided those patients into the laser guidance group and the freehand group. The primary outcome such as operation time, the number of ablation needle adjustments, postoperative pain scores, postoperative hospital stay, and postoperative complications were analyzed. Results The laser guidance group had a significantly shorter mean operation time compared to the freehand group (39.3 ± 13.65 min vs. 43.82 ± 19.12 min, p < 0.01), and in the laser guidance group, fewer ablation needle adjustments were required than in the freehand group (3.3 ± 1.34 time vs. 4.37 ± 1.39 times, p < 0.001). As compared to the freehand group, the laser guidance group had fewer cases of mild pneumothorax (13.16% vs. 38.33%, p < 0.05). The postoperative pain score at 1 h and 1 day of the two groups showed no statistical difference. Conclusion Both methods are safe and effective. The laser guidance technology significantly reduces the number of puncture adjustments and the operation time compared to the freehand method. Laser guidance technology effectively reduces the incidence of mild pneumothorax.